INSPECTION OF THE TECHNICAL CONDITION OF THE KHACHKAB HYDRAULIC SYSTEM AND RECOMMENDATIONS FOR INCREASING THE RELIABILITY OF THE STRUCTURE - Khasanov Khojiakbar Khamzayevich; Ahmetova Akdidar Kuralbayevna; Kosimjonova Malika Rustam qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation. The irrigation system of the Shakhrud canal is a large irrigation system of the Bukhara region, irrigating the entire left bank of the river. Zarafshan in the Bukhara oasis with the exception of the Abumuslim canal system. The Khachkab hydroelectric complex (water divider) is located in the middle reaches of the Shakhrud canal, which receives water from the Duaba water complex on the river. Zarafshan. Hydromechanical equipment - there are no DPZ and limit switches, on the 3rd gate there is no horizontal connecting shaft that connects the right and left lifting screws of the gate. Supply channel - inspect the bottom of the supply channel in the absence of water and draw up a report on the technical condition, and, if necessary, remove silt. Regulator of the left bank Shahrud canal - after stopping the water supply, carry out a technical inspection of the condition of the concrete parts of the structure and draw up a report on its technical condition.